Youth Agency and the Efficacy of Basic Education in Tanzania: An Inquiry into Post-primary School Structuration - DaSilva, Christian (Université d'Ottawa / University of Ottawa, 2015)
This qualitative study explores how youth in Tanzania, with low levels of basic education, manage their personal lives and seek opportunities in the workplace or in post-basic education training programs. In Tanzania, Education for All (EFA) has served as a key focal point of coordination between the government and the international donor community. While substantial attention has centered on the challenges of ensuring the sustainability and quality of EFA, there is relatively little known about the socio-economic circumstances of young school leavers and their perceptions of education and its relation to their post-school life trajectories. Using structuration theory as the theoretical framework to illuminate the dynamic interconnectedness of social structures and youth agency, I conducted semi-structured interviews with 14 young male and female school leavers. Disturbing patterns of social reproduction and a fundamental discontinuity between basic education and post-school challenges were revealed in the research. Yet, in view of their resilience, orientation to the future and entrepreneurial resourcefulness, findings suggest that despite profound qualitative shortcomings, aspects of basic education and the structuring effects of economic liberalization may be contributing to enhanced youth agency. The dissertation contributes to the theoretical discourse in the study of youth phenomena by adapting and advancing Klocker’s (2007) use of the notion of thinners and thickeners of agency within structuration theory. Exploring factors like educational quality and attainment level, in addition to those already established by Klocker (tribe, gender, age, and poverty), my research shows how young people’s agency can be attenuated or accentuated in space and time. This dissertation contributes empirical, hermeneutic and narrative data to illuminate the educational experience and post-basic education realities for a group of Tanzanian youth, reducing what has heretofore been described as a paucity of such qualitative accounts of marginalized African youth and the challenges they face.
Keywords: Education; Youth; Agency; Structuration; International Development; Aid; Africa; Youth bulge